(untitled) (Research, Society and Development, 2021)
Agroecology appears as a glow to the life of rural farmers, its base in sustainable production can guarantee a better quality of life for the rural population. This experience report seeks to expose perceptions obtained through work developed with a group of agroecological farmers, living in a community in the rural area of ​​the municipality of Cacoal-RO. The objective is to report an experience whose data were collected through experience and observation about the influence that agroecological practices had on improving the well-being of farmers and thus contributing to future research that adds to the capillarity of agroecological actions. The group of farmers is composed of 10 families who work directly with agroecology and actively participate in the activities. The group’s follow-up work was approximately 12 months. The perceptions analyzed in this report occurred simultaneously with the process of systematizing agroecological practices of the Bem Viver group, activities that were part of the execution of a master’s project. It is concluded that the work of the vegetable garden had a strong influence in improving the autonomy and well-being of the members of the group.